Isolated intramedullary spinal cysticercosis: A case report with review of literature of a rare presentation - Maste, Praful; Lokanath, Yadhu; Mahantshetti, Shambhulingappa; Soumya, S (Asian Journal of Neurosurgery, 2018)
A number of parasitic infections can involve the central nervous system of which neurocysticercosis (NCC) is the most common one in developing countries. Most often the brain is involved, spine and spinal cord involvement is very rare and intramedullary involvement is rarer still. Here, we report a 30-year-old male patient, with intramedullary NCC of dorsal spinal cord.
Keywords: Albendazole; parasitic infection; spinal intramedullary neurocysticercosis